An Interactive Approach to Enhancing Communication Skills of Elementary School Students within the QTM Framework - Muh. Khaerul Ummah BK; Nur Aisyah; Ilmawati N. Najib (Program Studi PGSD Universitas Madako Tolitoli, 2025)
Effective communication skills constitute a crucial foundation for the development of children’s social and academic competencies, making it essential to cultivate these skills from an early age in elementary education. This study aims to enhance students’ effective communication skills through the implementation of the Quantum Teaching Model (QTM), which is believed to foster interactive learning and improve students’ communicative abilities. The research employed a qualitative descriptive approach, involving 20 students from SD Negeri 2 Tambun, selected through representative sampling. Students were presented with open-ended problems requiring multiple solutions, thereby stimulating critical thinking and creativity. Data analysis was integrated with triangulation techniques through stages of data collection, simplification, categorization, presentation, and conclusion drawing. The results indicate an improvement in students’ communication skills across the dimensions of curiosity (13.40%), attitude (8.25%), competitiveness (12.89%), and external motivation (14.44%). These findings affirm that the implementation of QTM promotes more active and participatory learning interactions, thereby enhancing students’ communication skills and supporting the development of 21st-century competencies, particularly critical thinking, collaboration, and interactive communication. This study provides significant contributions to the development of QTM-based instructional strategies oriented toward improving students’ communication competencies and classroom interactions.